The healthy organisation: is it meaningful? - Oldenboom, Erna (Graduate School of Business (GSB), 2022)
In the thesis we have defined what is understood as a high health organization, and this in comparison with what is commonly known as a high performance organization. While much research is undertaken around high performance organizations, little or no research is undertaken around high health organizations. The thesis attempts to find answers to what it takes to be or to become a high health organization, and how organizations could create such a place, or possibly better “space”. Indeed, a high health organization is not a place, a building, or on organizational structure; it is a state of mind, a purpose, a form of coherence. The work in this thesis is by definition multidisciplinary and systemic, rooted in three, for the purpose, complementary research areas. Workplace spirituality is slowly making its recognition in the management literature, though still too much as a discipline in itself. Ayurveda, the thousands of years old wisdom tradition around systemic health, living systems and purposefulness does get some attention in academic work, however mainly within its cultural roots (of India). Finally, systemic thinking, not really mainstream yet either, is a scientific discipline that did find its way in the sciences, but is much less popular and use in management studies. As argued, we think that in the intersection of workplace spirituality, Ayurveda and systemics, a real new concept of a high health organization is emerging. Key concepts identified in the introduction were consciousness and coherence, which they play an important role in the entire thesis. The prevailing management research is based on an ontology of materialism, while it is clear that workplace spirituality, Ayurveda and systemics do not necessarily fit such an ontology. We have commented on an ontology of non-materialism, based on complexity theory and in particular the understanding of complex adaptive systems. If we would like to explore the concept of a high health organization, an adequate ontology (and epistemology) is necessary. It is impossible to develop a non-materialistic concepts within a materialistic ontology. The consequence of this ontological choice for our research methods are multiple and innovative. Our research method goes beyond deterministic causality, and attempts to visualize entanglement. It can only be based on a much more systemic analysis than what we are used to, hence we use Artificial Neural Networks and Semantics as analytical tools. Based on the results of our field research, the high health organization in a nutshell has the following components: 1. A systemic, values-based vision is the lighthouse of the high health organization 2. Values, and in particular lived values, are the driver of the high health organization 3. Transparent, clear, respectful and non-violent communication is the binding factor 4. A knowledge and learning culture is the necessary condition for a healthy organization 5. Organisational consciousness in the organization is the sufficient condition